Ясси игнадонли трикотаж тўқув машинасида олинган жаккард тўқималарида лайкра ипининг тўқима физик механик хусусиятларига таъсири тадқиқи - Oxunov Rustamjon Ne’matovich, Qurbanov Bohodir Mamadaliyevich, Xoliqov Kurbanali Madaminovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, using the capabilities of flat double-needle knitting machines, the production technology of adding lacquer yarn to patterned jacquard knitted fabric using local raw material, i.e., spun cotton yarn, was developed and its physical and mechanical parameters were researched. 3 samples of patterned jacquard knitted fabric were taken, their technological parameters and physical-mechanical properties were studied experimentally, presented in a table and analyzed. LONG XING LXA 252 12G double flat needle knitting machine produced experimental samples of patterned jacquard knitted fabrics and gave a graphic record.